Impact of Watershed Treatment on Water and Moisture Regime - A Case Study on Nachuninala and Pilasalki Watersheds (Orissa) - Ghosh, B.K.; Mahapatra, P.K.; Mahapatra, G. (Journal of Soil and Water Conservation, 2022)
Moisture conservation in situ is one of the major objective in watersheding and execution. In Orissa, the uplands are generally cultivated without any bunds and terraces leading to moisture stress and decrease in crop production. Though the total rainfall in most years is by and large sufficient for a mono upland crops, often there is "Agricultural drought". A case study was undertaken in the watershed area of Nachuni Nala and Pilasalki watershed of Orissa were extensive work on watershed basis have been taken up by availing assistance from the World Bank. The paper elaborates the increase in moisture and water regime in both the watersheds. The parameters that were studied are increase in depth of ground water level and waterspread area of reservoir lying in the watershed. Increase in yield specially in drought year was attributed to increase in moisture regime.